PRE-084 as a tool to uncover potential therapeutic applications for selective sigma-1 receptor activation. (September 2020) - Motawe, Zeinab Y.; Abdelmaboud, Salma S.; Cuevas, Javier; Breslin, Jerome W.
Abstract: The discovery of a highly selective putative sigma-1 (σ1) receptor agonist, PRE-084, has revealed the numerous potential uses of this receptor subtype as a therapeutic target. While much work has been devoted to determining the role of σ1 receptors in normal and pathophysiological states in the nervous system, recent work suggests that σ1 receptors may be important for modulating functions of other tissues. These discoveries have provided novel insights into σ1 receptor structure, function, and importance in multiple intracellular signaling mechanisms. These discoveries were made possible by σ1 receptor-selective agonists such as PRE-084. The chemical properties and pharmacological actions of PRE-084 will be reviewed here, along with the expanding list of potential therapeutic applications for selective activation of σ1 receptors.